Assassins - Donner, Richard, 1930-; Anatoli, Davydov; Antonio Banderas; Julianne Moore; Kelly Rowan; Muse Watson; Steve Kahan; Sylvester Stallone (USA, France Canal+, 1995)
Robert Rath (Sylvester Stallone) is a seasoned hitman who just wants out of the business with no back talk. But, as things go, it ain't so easy. A younger, peppier assassin named Bain (Antonio Banderas) is having a field day trying to kill said older assassin. Rath teams up with a computer hacker named Electra (Julianne Moore) to defeat the obsessed Bain.
Robert Rath (Sylvester Stallone) is a seasoned hitman who just wants out of the business with no back talk...
Andy Wachowski
Language : English Subtitles : English, French, Spanish, Italian, Dutch, Turkish, Polish,Portuguese, Hebrew, Czech, Icelandic
Keywords: Crime; Thriller; Action